Interactive Digital Media Based on Our-Space Website in Geography Learning : ICT, Media Skills, and Learning Styles - Dannis Ni'matussyahara; Sugiyanto Sugiyanto; Sarwono Sarwono (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to identify the availability of IT facilities and teacher characteristics towards the application of interactive digital multimedia, identification of media needs for students, and student learning styles in learning. This research was conducted at an alliance of geography teacher groups and two excellent schools in Surakarta City and Karanganyar Regency. The method used was descriptive qualitative with respondents consisting of 17 geography teachers of Surakarta City and 16 geography teachers of Karanganyar Regency, 34 students of grade XI of Surakarta 3 public high school, and 35 students of grade XI of Karanganyar 1 public high school. The data collection technique was carried out using observation techniques and questionnaires. The data analysis technique uses the Interactive Analysis Model, while the questionnaire analysis uses percentages. The results showed that: 1) teachers' experience in making IT-based media innovation and applying it in the classroom as much as 64.71% of geography teachers in Surakarta City and 81.25% of geography teachers in Karangayar Regency responded that they had never done it; 2) The need for digital-based multimedia as much as 94.12% of grade XI students in public high school 3 Surakarta and 100% of grade XI students in public high school 1 Karanganyar were interested in learning geography using integrative websites; 3) The average learning style characteristics of ninth-grade students in public high school 3 Surakarta and public high school 1 Karanganyar were 73% and 66% had a visual learning style. Based on the study's results, it was known that the low ICT skills of geography teachers could result in students' digital learning multimedia needs not being appropriately met, so integrative multimedia innovations such as the Our Space website are needed that can be tailored to student learning needs.